Estimation of design floods using univariate and multivariate flood frequency approach with regard to one wet year - Bezak, Nejc (Acta hydrotechnica, 2014)
The determination of design discharges and flood waves volumes is an important aspect of river engineering. The univariate annual maximum (AM), peaks-over-threshold (POT) and multivariate copula methods were used in this hydrologic study to investigate the impact of one wet year on the estimation of flood-related design variables. The flood frequency analyses (FFA) were performed using daily and hourly discharge data from three torrential streams in Slovenia where several flash floods occurred in the last decade. The results of the study indicate that the use of daily discharge data is inappropriate in case of torrential streams because the loss on information when compared to hourly hydrologic data is significant. The consideration of one wet year in the data sample has influence on the relationship between design variable and return period; however this influence is generally smaller than influence of the selected method to perform the FFA.
Keywords: annual maximums; climate change; copulas; flood frequency analyses; klimatske spremembe; kopule; metoda letnih maksimumov; metoda vrednosti nad izbranim pragom; peaks-over-threshold; verjetnostna analiza